2011
DOI: 10.1590/s1516-80342011000200010
|View full text |Cite
|
Sign up to set email alerts
|

O processamento auditivo e a combinação de traços distintivos na aquisição de fala em crianças com desvios fonológicos

Abstract: OBJETIVO: Investigar a relação entre as habilidades auditivas e as combinações de traços presentes na fala de crianças com desvios fonológicos. MÉTODOS: Participaram da pesquisa 22 crianças com diagnóstico de desvio fonológico, com idades entre 5 e 7 anos e de ambos os gêneros. Foi feita a coleta dos dados de fala por meio do teste Avaliação Fonológica da Criança. A combinação de traços foi observada mediante o Modelo Implicacional de Complexidade de Traços (MICT). Os traços adquiridos consideraram uma produçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
1
9
0
5
Order By: Relevance
“…In a study 10 , when analyzing the sequence of verbal sounds in the simplified CAP assessment, the authors observed that temporal ordering shows to be the skill that can be most compromised in children with alteration of distinctive features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study 10 , when analyzing the sequence of verbal sounds in the simplified CAP assessment, the authors observed that temporal ordering shows to be the skill that can be most compromised in children with alteration of distinctive features.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some studies have verified the importance of evaluating auditory discrimination in cases of PD, verifying the influence of all auditory skills in cases of phonological disorders 8,9 . In addition, several studies have already related PD and CAP, demonstrating, in general, that children with PD present alterations in auditory skills [4][5][6][7][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that all children had 100% success in the PSI, but in other tests used showed changes in temporal organization skills and figure-ground as well, lagged sensory memory, pointing out that such alterations can compromise the acquisition of these traits described 10 .…”
Section: Methodsmentioning
confidence: 97%
“…Extensive research, using the SSW test for evaluating AP, has been carried out on clinical populations assessing: difficulties in learning to read and write 1,4,[8][9][10][11] , the relationship between phonological disorder and AP [12][13][14][15][16][17][18] ; the relationship between oral breathing and the central auditory system 19 ; dyslexia 20 ; comorbidity between attention deficit hyperactive disorder (ADHD) and dyslexia 21 ; the relationship between performance in cognitive tests and AP tasks 22 ; listening skills in students aged 7 to 10 years, from different socioeconomic and cultural levels 23 and effectiveness of an informal program of specific auditory training for Auditory Processing Disorders (APD) in a group of 24 patients with this alteration.…”
Section: Methodsmentioning
confidence: 99%